An implicit effect of the health insurance portability and accountability act on medical tourism in India - Saurabh Mishra; Shashi kant Rai; Anushree Pandey; Vandana Jaiswal (UTMS Journal of Economics, 2013)
In today's world, the concept of implementing any standard is very much necessary for any nation to stand on a global level. Medical tourism is one of the most emerging industries in India. Many tourists from different nations travel across the world in order to reach India for medical facilities. There are several reasons for choosing this destination which includes reduced cost, lesser waiting time, well-trained Doctors and advanced technology as well. But at the same time, what hinders the growth of medical tourism in India is that the security measures in relation to data confidentiality and privacy is not up to the mark. There is a need for a specific and global standard so that the quality of service is improved which will also make the medical sector more reliable for the medical tourists here. U.S. is one of the major hosts in the field of medical tourism but the major problem is the high cost and long waiting queues. The major reason for choosing US as a place for availing medical services is the standard of services and a better level of data security. HIPAA (Health Insurance Portability and Accountability Act) was enacted in 1996 in the U.S.in order to protect the health related information of the patients. If any standard of such a nature is implemented in India then it will be a boom to the medical tourism industry in India. This paper deals with the benefits of implementing HIPAA in India, taking in course the share of Medical Tourism in the GDP of the Nation.
Keywords: I13; L83; 330; HIPPA; medical Tourism; Health industry; GDP